Cross-Cultural Intelligence in the Acquisition of Keigo: A Case Study of Indonesian Internship Students in Japan - Nunik Nur Rahmi Fauzah; Utami Rosalina; Sakania Dasabrina; Naylaa Dwi Aliyyah (MASI Mandiri Edukasi, 2025)
This study examines the role of cross-cultural intelligence in the acquisition of keigo (a variety of Japanese polite language) by Indonesian students participating in internship programs in Japan. With a qualitative approach, 9 participants from Institut Prima Bangsa and STBA Yapri were involved through questionnaires and interviews. The results show that students have high motivation to learn keigo, both for professional purposes and to maintain social relationships. Students' cross-cultural awareness can be seen from the understanding that keigo is a language skill as well as a cultural competence. The independent learning strategies used include memorizing, imitating supervisors, and utilizing digital media. The findings confirm that real interactions more influence the acquisition of skills in the workplace than learning in the classroom. This research emphasizes the importance of integrating cross-cultural intelligence in Japanese language learning and recommends the development of curriculum and internship programs based on real practices and digital technology.